Evaluasi Sistem Zonasi Untuk Keadilan Penerimaan Siswa Baru (Current Research in Education: Conference Series Journal, 2022)
Education in Indonesia is not evenly distributed, then the government makes a policy for schools to accept 90% of the quota for students who come from close by. But in practice, many things have been criticized and opposed by the community, even parents and students themselves. A little example is when a student wants to get a school with complete facilities but he is forced to go to a school near his house whose facilities are not complete, this will be a problem. The expected goal is to demand justice for students to get the same school facilities even though they are not favorite schools. The solution that can be done is an evaluation of the policy, which is reduced from 90% because it is too large, and before that the government should level the school facilities first before leveling the students. The method used is reviewing and collecting data from existing journals which are then reviewed and collected. The conclusion that can be accepted is that the zoning system policy needs evaluation, even though the goal is good but in practice it has not achieved this goal so it must be improved.